Efektivitas Board Game Interaktif dalam Meningkatkan Keterampilan Menulis Bahasa Arab Siswa Sekolah Dasar - Alia Maharani; Istikomah Difinubun; Melinda Cahyani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effectiveness of interactive board game learning media in improving Arabic writing skills among fifth-grade students at MI Islamiyah 02 Madiun. The research employs a quantitative approach using a quasi-experimental design involving an experimental group and a control group with a total sample of 47 students. Data were collected through pretest and posttest instruments and analyzed using the Mann–Whitney U test with the assistance of SPSS software. The findings reveal a statistically significant difference between the experimental and control groups, with a significance value of 0.000 (<0.05). Students in the experimental group demonstrated higher improvement in writing skills compared to those in the control group. The use of interactive board game media enhances student motivation, engagement, and participation in learning activities. This study implies that game-based learning media can serve as an effective alternative for improving Arabic writing skills at the elementary school level.